EPEN-16. PATIENT-DERIVED PFA EPENDYMOMA XENOGRAFT MODEL. Issue 2 (22nd June 2018) - Griesinger, Andrea; Pierce, Angela; Witt, Davis; Flannery, Patrick; Donson, Andrew; Gowan, Katherine; Hankinson, Todd; Handler, Michael; Jones, Kenneth; Green, Adam; Vibhakar, Rajeev; Foreman, Nicholas
Abstract: Advances in ependymoma (EPN) treatment have been hampered due to lack of relevant in vitro and in vivo models. Our lab successfully generated patient derived posterior fossa group A (PFA) EPN cell lines. Our present goal is to establish patient derived xenograft (PDX) mouse models. Disaggregated cells from a primary PFA tumor (811) were injected subcutaneously into NSG mice flanks forming tumors 8 months post injection. Tumors were confirmed as EPN by typical histologic features by a neuropathologist. This flank tumor was successfully used to establish monolayer cell lines. 850K methylation array on flank tumor showed the same chromosome abnormalities as the primary tumor, including gain of 1q. Transcriptomic clustering analysis showed that flank tumor grouped with PFA EPN primary tumors. Flank tumor cells were disaggregated into single cell suspension and serially injected both subcutaneous and intracranial. Serial flank tumors formed within 2 months of injection. MRI imaging of one intracranial injected mouse showed a large mass in the cerebellum. Additionally, before MRI scans could be performed, a second symptomatic mouse with intra-ventricle injection was euthanized. Necropsy revealed an encapsulated mass between the midbrain and cerebellum and histology confirmed classic EPN features. This mass was serially transplanted into lateral ventricle of several additional mice. In addition to MAF811_5, we have preliminary evidence, that needs to be confirmed, that 2 further EPN tumors have established flank xenografts and cell lines. These PDXs are promising in showing the feasibility of establishing PFA xenograft models together with matching cell lines.